2011
DOI: 10.1074/jbc.m111.254268
|View full text |Cite
|
Sign up to set email alerts
|

CX3CR1 Protein Signaling Modulates Microglial Activation and Protects against Plaque-independent Cognitive Deficits in a Mouse Model of Alzheimer Disease

Abstract: Aberrant microglial activation has been proposed to contribute to the cognitive decline in Alzheimer disease (AD), but the underlying molecular mechanisms remain enigmatic. Fractalkine signaling, a pathway mediating the communication between microglia and neurons, is deficient in AD brains and down-regulated by amyloid-␤. Although fractalkine receptor (CX3CR1) on microglia was found to regulate plaque load, no functional effects have been reported. Our study demonstrates that CX3CR1 deficiency worsens the AD-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
213
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(223 citation statements)
references
References 51 publications
9
213
0
1
Order By: Relevance
“…Unexpectedly, however, this resulted in reduced amyloid pathology. These findings were confirmed in additional AD mouse models [96,97]. Using in vivo 2-photon imaging, Fuhrmann et al [98] showed that in the 5XFAD model of AD, homozygous loss of CX3CR1 impaired microglia recruitment to areas of neuronal death.…”
Section: Cx3cr1/cx3cl1supporting
confidence: 60%
See 1 more Smart Citation
“…Unexpectedly, however, this resulted in reduced amyloid pathology. These findings were confirmed in additional AD mouse models [96,97]. Using in vivo 2-photon imaging, Fuhrmann et al [98] showed that in the 5XFAD model of AD, homozygous loss of CX3CR1 impaired microglia recruitment to areas of neuronal death.…”
Section: Cx3cr1/cx3cl1supporting
confidence: 60%
“…However, in the hTau model of AD, while CX3CR1 deficiency still enhanced inflammation, it also promoted increased levels of phosphorylated and insoluble tau species [99]. CX3CR1-deficient AD mice also had impaired performance in spatial learning tasks [96,99]. Thus, CX3CR1/L1 signaling shifts microglia away from a pro-inflammatory phenotype, but this has disparate effects on different aspects of AD pathology-reducing amyloid pathology on the one hand, while enhancing tau pathology on the other.…”
Section: Cx3cr1/cx3cl1mentioning
confidence: 99%
“…These neuronal ligands correspond to specific receptors on microglia, namely, fractalkine receptor (CX3CR1), CD172 (SIRP-1α), and CD200R. A lack of these ligands on neurons or a lack of the corresponding receptors on microglia greatly impacts microglial function and activation [26,27]. These observations contributed to the conclusion that microglia are actively monitoring (or surveilling) neuronal health status and react when they sense an alteration in their environment.…”
Section: Introductionmentioning
confidence: 82%
“…Surprisingly, Cx3cr1 knockout did not affect the activation of microglia as assessed by morphological alteration and by cytokine expression. Whilst Cx3cr1 knockout experiments in Parkinson's disease, ALS and Alzheimer's disease models have indicated a role for CX3C signalling (Cardona et al, 2006;Lee et al, 2010;Cho et al, 2011), our experiments suggest that CX3CR1 is not essential to the microglial response in prion disease. As others have proposed, some redundancy may exist in the signalling mechanisms that regulate microglia (Biber et al, 2014), thus other molecules such as CD200/CD200R and/ or TREM2 may play an augmented role upon deletion of Cx3cr1 in prion disease models.…”
mentioning
confidence: 81%
“…Elevated cytokine levels in the brain of scrapie-infected mice at clinical time point. Using multiplex immunoassays, protein levels of 23 cytokines [eotaxin, granulocyte colony stimulating factor, granulocyte/macrophage colony stimulating factor, , IL-12(p70), IL-13, IL-17A, KC, CCL2, CCL3, CCL4, neurodegeneration, such as Alzheimer's disease, Parkinson's disease and ALS, knockout of Cx3cr1 produced significant differences in microglial activation and cytokine profile in brain (Limatola & Ransohoff, 2014;Lee et al, 2010;Cho et al, 2011). In our experiments, elevated levels of 10 of the 23 cytokines tested were detected in both RML-and 22L-inoculated Cx3cr1-KO and C57 mice compared with mock controls (Fig.…”
mentioning
confidence: 99%